2003
DOI: 10.1097/01.ju.0000050221.51509.f5
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Place for Radical Nephrectomy in the Presence of Metastatic Collecting Duct (Bellini) Carcinoma?

Abstract: Most collecting duct carcinomas are already metastatic at presentation. Because the prognosis is dismal despite radical nephrectomy, biopsy should be performed first when radiological findings are suggestive of collecting duct carcinoma. For metastatic collecting duct carcinoma radical nephrectomy alone does not seem to be useful except for palliative reasons or in the framework of new multicentric chemotherapy protocols in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 19 publications
0
43
0
10
Order By: Relevance
“…It is important to note that the invasive nature of cdc tumours, combined with the poor preoperative performance status of cdc patients, results in an elevated rate of perioperative morbidity and mortality. For example, Mejean et al 23 reported 3 perioperative deaths in their series of 10 patients undergoing surgery for cdc. Surgical complications and recovery may also delay or prevent a patient from receiving systemic therapy 11 .…”
Section: 21mentioning
confidence: 99%
“…It is important to note that the invasive nature of cdc tumours, combined with the poor preoperative performance status of cdc patients, results in an elevated rate of perioperative morbidity and mortality. For example, Mejean et al 23 reported 3 perioperative deaths in their series of 10 patients undergoing surgery for cdc. Surgical complications and recovery may also delay or prevent a patient from receiving systemic therapy 11 .…”
Section: 21mentioning
confidence: 99%
“…In our case there was no point in undertaking further surgical intervention (resection of the retroperitoneal or bone metastasis), as these interventions have no effect on survival or on quality of life. 3,6,8 Immunohistochemical examinations are very important for the diagnosis procedure of anaplastic tumors, because haematoxylin-eosin slides alone are not enough to establish the origin of the tumor. The result of immunohistochemical examinations can be misleading in certain cases, including our case, since the first histological result suggested anaplastic transitional cell cancer because of the morphological structure of the haematoxylin-eosin slides and the vimentin negativity.…”
Section: Discussionmentioning
confidence: 99%
“…It is often already metastatized at the time of diagnosis, and its prognosis is rather poor. 6 The tumor gives lymphogeneous metastases to the paraaorical and paracaval lymphnodes, while haematogeneously the liver, lung and bone are the predilection sites of the metastases. The primary tumor is symptomless, the first symptoms are bone metastases or loss of weight of an advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrectomy is not recommended in patients with ganglionary affectation or distant metastasis with an expected survival less than a year given the major perioperative risk involved [6].…”
Section: Archives In Cancer Research Issn 2254-6081mentioning
confidence: 99%